Genomic footprints related with adaptation and fumonisins production in Fusarium proliferatum - Wang, Ling; Liu, Qing; Ge, Shuailing; Liang, Wenhao; Liao, Weiyang; Li, Wen; Jiao, Guiai; Wei, Xiangjin; Shao, Gaoneng; Xie, Lihong; Sheng, Zhonghua; Hu, Shikai; et al. (Frontiers in Microbiology, 2022)
Fusarium proliferatum is the principal etiological agent of rice spikelet rot disease (RSRD) in China, causing yield losses and fumonisins contamination in rice. The intraspecific variability and evolution pattern of the pathogen is poorly understood. Here, we performed whole-genome resequencing of 67 F. proliferatum strains collected from major rice-growing regions in China. Population structure indicated that eastern population of F. proliferatum located in Yangtze River with the high genetic diversity and recombinant mode that was predicted as the putative center of origin. Southern population and northeast population were likely been introduced into local populations through gene flow, and genetic differentiation between them might be shaped by rice-driven domestication. A total of 121 distinct genomic loci implicated 85 candidate genes were suggestively associated with variation of fumonisin B1 (FB1) production by genome-wide association study (GWAS). We subsequently tested the function of five candidate genes (gabap, chsD, palA, hxk1 and isw2) mapped in our association study by FB1 quantification of deletion strains, and mutants showed the impact on FB1 production as compared to the wide-type strain. Together, this is the first study to provide insights into the evolution and adaptation in natural populations of F. proliferatum on rice, as well as the complex genetic architecture for fumonisins biosynthesis.